Lease: Problematic Aspects of Accounting and Reporting Information Formation - T. Yu. Druzhilovskaya; E. S. Druzhilovskaya (Учёт. Анализ. Аудит)
In the light of the recently adopted new Russian and international standards in accounting and tax accounting, significant changes in the regulation of lease accounting have been made. Unfortunately, the newly adopted rules are not always ideal in terms of their practical application. The article is devoted to a critical analysis of the regulations of the international standard IFRS (IFRS) 16 “Lease” and the Russian standard FSBU25/2018 “Lease Accounting.” The methodological basis of the study includes a critical analysis of the new requirements for accounting for lease transactions in the systems of Russian and international standards in terms of their validity, logic and completeness. The result of the study is the justification of the presence of both positive and problematic aspects in the innovations introduced in the regulation of accounting for leases in IFRS16 and in the Russian standard FSBU25/2018. Recommendations have been made to address the problematic issues of lease accounting and reporting information. The theoretical and practical significance of the study lies in the possibility of using its results in the preparation of new and improved existing accounting regulations in the process of its further development at the national and international levels.